GE_GERICHTE P/10454/2011 vom 3. Mai 2012 - GE Cour de justice (2012)
; VOL(DROIT PÉNAL) ; INFRACTION D'IMPORTANCE MINEURE ; TRAVAIL D'INTÉRÊT GÉNÉRAL ; INDEMNITÉ(EN GÉNÉRAL) ; PLAIGNANT | CP.139; CP.172.ter; CP.37; CPP.433